Brain Abscess: Surgical Removal and Quality of Life - A Comprehensive Review - Banin Yousef Abdulla Alhajji et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Brain abscess, a localized collection of pus within the brain parenchyma, is a rare but life-threatening condition. Advances in neurosurgical techniques, imaging modalities, and antibiotic therapy have significantly improved survival rates. However, the long-term impact on patients' quality of life (QoL) remains an area of concern due to potential neurological deficits, cognitive impairments, and psychological challenges. This review examines the surgical management of brain abscesses, its outcomes, and the subsequent impact on QoL, while highlighting areas for future research. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/267 https://doi.org/10.5281/zenodo.14270552